Correction: Experimental and theoretical charge density distribution in Pigment Yellow 101. Issue 9 (7th March 2015) - Du, Jonathan J.; Váradi, Linda; Tan, Jinlong; Zhao, Yiliang; Groundwater, Paul W.; Platts, James A.; Hibbs, David E.
<x xml:space="preserve">Abstract</x> Correction for 'Experimental and theoretical charge density distribution in Pigment Yellow 101' by Jonathan J. Du et al., Phys. Chem. Chem. Phys., 2015, DOI: ; Web: 10.1039/c4cp04302b.